Building ethical virtual classrooms: Confucian perspectives on avatars and VR - Chi-Ming Lam (Computers & Education: X Reality)
This paper examines the ethical implications of using avatars and virtual reality (VR) in education, focusing on issues such as privacy, identity representation, psychological impact, equity in access, and virtual bullying. Confucian ethics, emphasizing virtues like benevolence (ren), righteousness (yi), ritual propriety (li), wisdom (zhi), trustworthiness (xin), and loyalty (zhong), offers a valuable framework for addressing these challenges. Applying these principles, educators and policymakers can create environments that prioritize student well-being and moral development. By integrating Confucian ethics with contemporary ethical frameworks, including deontology, utilitarianism, and virtue ethics, this paper argues for more robust and comprehensive ethical guidelines. The holistic approach of Confucian ethics ensures respect for students’ identities, mental well-being, and equitable learning opportunities. Ultimately, fostering a culture of virtue, respect, and inclusivity can lead to a more ethical and harmonious educational landscape with the responsible use of educational technology.